New species of Zygoclistron Rehn, 1905 (Insecta: Orthoptera: Acrididae: Copiocerinae) in the central corridor of the Atlantic Forest biome - Silva, Daniela Santos Martins; Pereira, Marcelo Ribeiro; Domenico, Fernando Campos De; Sperber, Carlos Frankl (Zootaxa, 2016)
Herein we describe a new species of Copiocerinae, Zygoclistron ruschii Silva n. sp., from Atlantic Forest remnants in southeastern Brazil, collected from the Reserva Biológica Augusto Ruschi in the Santa Teresa municipality, Espírito Santo state, Brazil. The diagnosis of this new species is based on phallic complex and terminalia characters.